Legal Analysis of Legal Protection for Children as Victims of Sexual Harassment (Case Study: PPA Unit, Semarang Police) - Mulyono, Novendra Fajar Mulyono; Wahyuningsih, Sri Endah (Jurnal Hukum Khaira Ummah, 2025)
This study aims to analyze legal protection for children as victims of sexual harassment, with a focus on handling by the Women and Children Protection Unit (PPA) of the Semarang Police. Legal protection for child victims of sexual violence is very important considering the psychological and social impacts it causes. The method used in this study is sociological juridical, with a qualitative approach to research specifications in the form of analytical descriptive. Data sources consist of primary data, secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. The results of the study show that the Semarang Police through the PPA Unit have made legal protection efforts through a fast investigation process, psychological and legal assistance, and coordination with related agencies such as the Social Service and Child Protection Agency. However, there are still obstacles such as limited number of experts, lack of supporting facilities, and lack of public understanding of the importance of reporting cases of sexual abuse against children. Therefore, better synergy between institutions is needed as well as increased education and socialization to the community to create optimal protection for children.